2015
DOI: 10.3382/ps/peu059
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilization and growth performance of chickens fed novel wheat inbred lines selected for different pentosan levels with and without xylanase supplementation

Abstract: Different F5 recombinant inbred lines from the cross Yumai 34 × Ukrainka were grown in replicated trials on a single site in one harvest year at Rothamsted Research. A total of 10 samples from those lines were harvested and used in a broiler experiment. Twenty nutritionally complete meal-form diets that had 630 g/kg of wheat with different amounts of pentosan, with and without exogenous xylanase supplementation, were used to compare broiler growth performance and determine apparent metabolizable energy correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…Because of its digestive capacity, xylanase attracts the attention as a candidate for improving the efficiency of feed utilization and degrading NSPs in feed ingredients of plant origin (Bedford & Schulze, ). Although xylanase has been used extensively in the poultry (Pirgozliev et al, ) and livestock (Prandini et al, ) industries to enhance energy and nutrient availability in plant ingredients, little is known about its application in aquaculture. Recently, the use of exogenous carbohydrases in aquafeed has attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its digestive capacity, xylanase attracts the attention as a candidate for improving the efficiency of feed utilization and degrading NSPs in feed ingredients of plant origin (Bedford & Schulze, ). Although xylanase has been used extensively in the poultry (Pirgozliev et al, ) and livestock (Prandini et al, ) industries to enhance energy and nutrient availability in plant ingredients, little is known about its application in aquaculture. Recently, the use of exogenous carbohydrases in aquafeed has attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…() and Pirgozliev et al . () showed that the beneficial effects of the addition of NSP enzymes on the digestibility of wheat‐ and soybean meal‐based diets have been widely investigated. Furthermore, Williams et al .…”
Section: Introductionmentioning
confidence: 99%
“…NSP enzymes also allow a larger proportion of inclusion and even reduce the negative effects of low-quality plant ingredients in monogastric diets, contributing to cost reductions as well as increased formulation flexibility (Zijlstra et al 2010;Lafond et al 2011). Kiarie et al (2014) and Pirgozliev et al (2015) showed that the beneficial effects of the addition of NSP enzymes on the digestibility of wheat-and soybean meal-based diets have been widely investigated. Furthermore, Williams et al (2014) highlighted the possible use of these enzymes to increase the nutritional value of low-energy diets, thus allowing a reduction of the AME without compromising birds' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Research on feeding value of wheat for poultry is well documented (Gutierrez-Alamo et al, 2008;Ball et al, 2013;Pirgozliev et al, 2015). However, there is inconsistence in the literature as some of the authors report responses on growth performance and nutrient availability to mash diets (Scott et al, 1998;Rose et al, 2001;Steenfeldt, 2001;Pirgozliev et al, 2003), others reported responses to pelleted diets (Wiseman et al, 2001;Carre et al, 2005).…”
Section: Introductionmentioning
confidence: 99%